المسؤولية الاجتماعية وعلاقتها بمفهوم تمايز الذات لدى طالبات قسم رياض الاطفال (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the social responsibility of female students in the kindergarten department and identify self-differentiation and the correlation between social responsibility and self-differentiation. The researcher used the descriptive correlational approach and the sample consisted of (200) female students from the kindergarten department, a delegation. The researcher prepared a social responsibility scale and adopted the (Shakir) scale. (2024) for self-differentiation, and using appropriate statistical methods, the results showed that female students enjoy social responsibility and self-differentiation, and that there is a correlation between responsibility and self-differentiation.